Use of Cognitive Interviews to Test the Validity of a Reading Motivation Instrument for English Learners. Issue 8 (16th November 2020) - Jang, Bong Gee; Protacio, Maria Selena
Abstract: This cognitive interview study aims to improve the content validity of a newly developed reading motivation instrument for English learners. Previous research has shown there is a significant need for survey developers to conduct cognitive interviews to ensure that in real world settings survey respondents interpret the items as the framers intended. The proposed study focuses on six main patterns of student misinterpretation that could suggest the need for further revision of survey items in order to improve their content and item validity: lexical ambiguity, unclear referential scope, inapplicability, long recall period, complex judgment, and cultural variation. Further implications and suggestions were discussed in relation to both classroom practice and future research.